Towards a framework for building security operation centers - Jacobs, Pierre Conrad (Rhodes University, Faculty of Science, Department of Computer Science, 2015)
In this thesis a framework for Security Operation Centers (SOCs) is proposed. It was developed by utilising Systems Engineering best practices, combined with industry-accepted standards and frameworks, such as the TM Forum's eTOM framework, CoBIT, ITIL, and ISO/IEC 27002:2005. This framework encompasses the design considerations, the operational considerations and the means to measure the effectiveness and efficiency of SOCs. The intent is to provide guidance to consumers on how to compare and measure the capabilities of SOCs provided by disparate service providers, and to provide service providers (internal and external) a framework to use when building and improving their offerings. The importance of providing a consistent, measureable and guaranteed service to customers is becoming more important, as there is an increased focus on holistic management of security. This has in turn resulted in an increased number of both internal and managed service provider solutions. While some frameworks exist for designing, building and operating specific security technologies used within SOCs, we did not find any comprehensive framework for designing, building and managing SOCs. Consequently, consumers of SOCs do not enjoy a constant experience from vendors, and may experience inconsistent services from geographically dispersed offerings provided by the same vendor.
Keywords: Security systems industry; Systems engineering; Expert systems (Computer science); COBIT (Information technology management standard); Computer security